2017
DOI: 10.9734/jeai/2017/33807
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Agronomic Potential of Androgenic Pepper Genotypes Derived from Piran (Capsicum annuum L. cv. Piran)

Abstract: Aims: This study was to evaluate and estimate the agronomic potential of two androgenic genotypes via important plant, fruit and production traits compared to the mother genotype Piran. Place and Duration of Study: Strumica, Faculty of Agriculture, Goce Delcev University-Stip, Republic of Macedonia, four-years experiment. Methodology: The experiment was set up in random block design in four replications. Evaluation of the androgenic genotypes was performed according to morphological traits given in Descriptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…[23], which reported higher pericarp thickness of genotypes grown in conventional production, than those cultivated in organic production. The results of other researchers showed that the average fruit flesh ranged from 76 to 77% for Piran and its two androgenic lines grown under protected conditions, which is in accordance with our results [18]. In the investigated lines of the Kurtovska Kapija (KK1 and KK2), this value was 78 to 79%, which is less than it is found in our experiment [20].…”
Section: Table 2 Pairwise Comparison Between A) Plant Height and Culsupporting
confidence: 91%
See 1 more Smart Citation
“…[23], which reported higher pericarp thickness of genotypes grown in conventional production, than those cultivated in organic production. The results of other researchers showed that the average fruit flesh ranged from 76 to 77% for Piran and its two androgenic lines grown under protected conditions, which is in accordance with our results [18]. In the investigated lines of the Kurtovska Kapija (KK1 and KK2), this value was 78 to 79%, which is less than it is found in our experiment [20].…”
Section: Table 2 Pairwise Comparison Between A) Plant Height and Culsupporting
confidence: 91%
“…The results in this study differ from the results published by López et al [23] where the investigated genotypes produced in the organic production system have a higher fruit index compared to those in the conventional system. Also, Kurtovska Kapija and Piran have a lower index of fruit compared to the results of this experiment [18,20].…”
Section: Table 2 Pairwise Comparison Between A) Plant Height and Culmentioning
confidence: 51%
“…During the first experimental year seeds obtained from fertile androgenic plants were utilized as starting material in the experiment. Seeds from selected typical fruit from each androgenic genotype of the previous experimental year were used in the subsequent experimental years [10,15].…”
Section: Research Design and Dynamicsmentioning
confidence: 99%
“…Plants were cultivated according to standard cultivation practices under protected conditions. Irrigation and nutrition were performed as fertigation with drip system [10,15].…”
Section: Research Design and Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation